Child Rights And Gender-Based Violence: Cross-National Analysis: A Punjab, Pakistan Case Study - Dr. Sadia Rafi; Dr. Mumtaz Ali (Social Science Review Archives, 2025)
Although most countries have signed the United Nations Convention on the Rights of the Child (CRC), it has become nearly universal, and the level of violence against children and gender-based violence (GBV) has become so pervasive and entrenched in society. It is estimated globally that one billion children are subject to physical, sexual, or emotional violence annually and that one out of three women in the world population have been subjected to physical and /or sexual intimate partner violence. Research Objectives of this study are: To consider how the child rights violations and gender-based violence are interdependent in a cross-national setting in the country of Punjab, Pakistan. To determine and evaluate the socio-cultural, economic and institutional reasons that lead to the continuation of child rights abuse and gender-based violence in Punjab. To determine how the current legal systems, child protection systems, and policy-based interventions have worked to tackle gender-based violence and child rights protection in Punjab. To provide evidence-based policy suggestions and strategic interventions based on the best practices in other countries to enhance child protection systems and gender equity in Punjab, Pakistan. The research design utilized in this study was qualitative in nature in an attempt to understand the intersection point between child rights and gender-based violence on a cross-national analytical study, as applied to the case study of Punjab, Pakistan. This study was informated by an interpretivist paradigm with the acknowledgment that, social realities of violence and rights are culturally fashioned and constructed by cultural meanings. The study took place in Punjab, Pakistan, which is the most populous province of this country, and which has different socio-economic and cultural processes. The country of Punjab has recorded a large percentage of cases of child abuse and gender-based violence in the national rereader and thus, it is a vital location in qualitative research. Key stakeholders who participated in child protection and gender base violence response mechanisms formed the target population. An example of a purposive sampling methodology was used to choose those participants whose knowledge and experience were directly linked to child rights and gender base violence. This approach was used to make sure the data-rich cases can be included that can give in-depth information. A sample of about 15-25 participants was used in order to bring about data saturation that would guarantee depth and credibility of the findings. The semi-structured interviews were long-form in-depth interviews that were created in relation to the objective of the research through an interview guide.